(untitled) (Media Kesehatan Masyarakat Indonesia, 2020)
Pregnant women experience significant changes in physiological and psychological functions. The process of adjusting to this new condition often causes anxiety. One of the pregnancy complications that is affected by anxiety is preeclampsia. The purpose of this study was to identify the effects of antenatal yoga and murottal Al-Quran therapy on pregnant women at risk of preeclampsia. This study was conducted in primary health care in Majalengka, Indonesia, using true experiment (pretest-posttest control group) design as many 40 respondents divided into 4 groups, Antenatal Yoga (AY), the Murottal Al-Qur’an Therapy (MAT), combination of yoga and murottal al-Quran, and control group. Respondents were taken by cluster and simple random sampling. The anxiety, blood pressure, sFlt-1, and PIGF levels of all respondents were measured after 12 interventions. Data were analyzed with Kruskall-Wallis and One-way Anova tests. The antenatal yoga, murottal Al-Qur’an therapy, and its combination significantly decrease anxiety (p=0.007), systole (p=0.006), and diastole (p=0.001) in pregnant women with the risk of preeclampsia. There were no significant differences of sFlt-1 (p=0.286), PIGF (p=680) and ratio of sFlt-1/PIGF (p=969) among groups. The antenatal yoga, Murottal Al-Qur’an therapy, and it’s combination effect decreasing anxiety and blood pressure in pregnant women with the risk of preeclampsia in Majalengka.